Effect of Cationic Groups on the Selectivity of Ternary Antimicrobial Polymers. Issue 21 (4th November 2022) - Pham, Phuong; Oliver, Susan; Nguyen, Duong Thanh; Boyer, Cyrille
Abstract : Back Cover : In article 2200377, Cyrille Boyer and co‐workers show the antimicrobial polymers as a promising approach to combat multidrugresistant pathogens. A library of 31 amphiphilic ternary polymers containing different cationic groups, including primary amine, guanidine, and sulfonium groups, is prepared to investigate the impact of cationic groups on antimicrobial activity and cytotoxicity against mammalian cells.